Prevalence of Common Mental Disorders in South Asia: A Systematic Review and Meta-Regression Analysis - Naveed, Sadiq; Waqas, Ahmed; Chaudhary, Amna Mohyud Din; Kumar, Sham; Abbas, Noureen; Amin, Rizwan; Jamil, Nida; Saleem, Sidra (Frontiers in Psychiatry, 2020)
South Asian countries report the highest prevalence of common mental disorders globally. This systematic review and meta-analysis report the pooled prevalence of common mental disorders among the South Asian countries. Database searches were conducted in eight electronic databases. Titles, abstracts, full-text screening, and extraction of data on the event rate of 17 indicators of common mental disorders were performed by two independent reviewers. 160 studies were included and data analysis was done using the Comprehensive Meta-analysis Software (v.3). A 10-year prevalence of depressive symptoms was 26.4% among 173449 participants, alcohol abuse was 12.9% (n=107893); anxiety 25.8% (n=70058); tobacco smoking 18.6% (n=84965); PTSD 17.2% (n=42298); mixed anxiety and depression 28.4% (n=11102); suicidal behaviors 6.4% (n=25043); misuse of opiates 0.8% (n=37304); tobacco chewing 21.0% (n=10586); use of cannabis 3% (n=10977); GAD 2.9% (n=70058); bipolar disorder 0.6% (n=7197); IV drug abuse 2.5% (n=15049); panic disorder 0.01% (n=28087); stimulant use 0.9% (n=1414); OCD 1.6% (n=8784) and phobic disorders 1.8% (n=27754). This study reported a high ten-year prevalence of common mental disorders in South Asian countries; necessitating further research on psychiatric epidemiology in those contexts. It informs the need for effective policymaking and implementation of culturally appropriate multilevel interventions.